1995
DOI: 10.1074/jbc.270.37.21942
|View full text |Cite
|
Sign up to set email alerts
|

The Human Lumican Gene

Abstract: A human lumican cDNA sequence was derived by polymerase chain reaction techniques from RNA obtained from intestine, placenta, and articular cartilage. A contiguous sequence of 1729 bases was obtained corresponding to an observed message size of 1.8 kilobases (kb). The cDNA sequence consists of an 80-base pair (bp) 5-untranslated region, a 1014-bp coding sequence, and a 618-bp 3-untranslated region terminating in a 17-bp poly(A) tail. The deduced lumican protein sequence has 338 amino acids, including a putativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
90
1
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(93 citation statements)
references
References 43 publications
0
90
1
2
Order By: Relevance
“…3,8,13,20 In the adult cornea, lumican exists as PG; however, in the embryonic cornea, lumican is reported to be localized as a glycoprotein. The change from glycoprotein to PG may have an important role in corneal transparency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,8,13,20 In the adult cornea, lumican exists as PG; however, in the embryonic cornea, lumican is reported to be localized as a glycoprotein. The change from glycoprotein to PG may have an important role in corneal transparency.…”
Section: Discussionmentioning
confidence: 99%
“…21 In the human juvenile cartilage, all lumican exists as a keratan sulfate PG; however, in the adult most of the lumican exists as a glycoprotein form that is devoid of polylactosamine chains. 3,22 The core protein of lumican is reported to affect collagen fibrillogenesis. 23 However, little is known about the role of the glycosyl side chains of lumican protein.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Class I, members of Class II SLRPs are encoded by three exons, with all ten LRRs encoded by a single large exon (222,223). In these genes, the introns are positioned at identical sites, just proximal to the translation initiation and termination codons, respectively (223).…”
Section: Genomic Organization and Transcriptional Controlmentioning
confidence: 99%
“…In corneal stroma, lumican is a KSPG, whereas lumican presents as an under-or unglycanated glycoprotein in other tissues (9,13,14,21). It has been proposed that the horseshoe-shaped lumican core protein binds collagen molecules to modulate collagen fibril diameter, whereas the N-linked glycosaminoglycan chains regulate fibril spacing and stromal hydration for the formation and maintenance of transparent corneas (22)(23)(24).…”
mentioning
confidence: 99%
“…biglycan (Xq27ter), decorin (12q21-22), lumican (12q21. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], and DSPG3 (12q21) (4 -9). Our previous study showed that certain variations (rs3759223 (C3 T)) of single nucleotide polymorphism in the lumican regulatory region may influence the promoter activities of lumican and affect fibrillogenesis in myopic eyes (10).…”
mentioning
confidence: 99%